Multifunctional HDPE/CNTs/PW composite phase change materials with excellent thermal and electrical conductivities - Li, Xiaolong; Sheng, Xinxin; Guo, Yongqiang; Lu, Xiang; Wu, Hao; Chen, Ying; Zhang, Li; Gu, Junwei (Journal of materials science & technology, 2021)
The fabricated multifunctional composite PCMs possesses high energy storage density, excellent light-to-thermal conversion and electro-to-thermal conversion effect. [Display omitted] •The HDPE/CNTs porous scaffolds were successfully fabricated via sacrificial template method.•HDPE/CNTs/PW-3:7 obtained possesses high melting enthalpy (153.95 J/g).•The thermal conductivity and electrical conductivity of HDPE/CNTs/PW-3:7 are increased greatly.•HDPE/CNTs/PW-3:7 possesses huge potential in the field of multifunctional thermal energy storage. The risk of leakage and low thermal conductivity severely hinder the wide application of phase change materials (PCMs). In this work, the high-density polyethylene/carbon nanotubes (HDPE/CNTs) porous scaffolds were successfully fabricated via a sacrificial template method followed by the general melt blending and water solvent etching. Subsequently, a series of paraffin wax HDPE/CNTs/PW composite PCMs were obtained combined with the simple vacuum impregnation method. The obtained HDPE/CNTs porous scaffolds can effectively avoid the leakage of PW, meanwhile, the thermal conductivity and electrical conductivity of HDPE/CNTs/PW-3:7 are increased by 2.94 times and 13 orders of magnitude compared with the HDPE/PW-3:7 respectively, also, it exhibits high phase change enthalpy (153.95 J/g for melting enthalpy and 152.82 J/g for crystallization enthalpy). From the above perspectives, the HDPE/CNTs/PW-3:7 has promising potential value in the application of light-to-thermal conversion, electro-to-thermal conversion and thermal energy storage.